PRELIMINARY PHYTOSOCIOLOGICAL SURVEY OF POACEAE DIVERSITY IN BAUCHI STATE UNIVERSITY GADAU, MAIN CAMPUS - ADAMU, MUSA; MOHAMMED A. U; ABUBAKAR, BASHIR MOHAMMED; ZIGAU, ZAINAB AUWAL (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
The Grass family of Poaceae is one of the largest and ecologically important plant families in the tropics and temperate region with about 11,000 species occupying almost all habitats on all continents. It is very necessary to have information about the family Poaceae which is need to serve as a biodiversity data base assessable for further research. Different sampling points were selected based on the presence of members of the family Poaceae and 1m x 1m quadrat was thrown at three random points in each sampling point; Frequency, Relative frequency, Cover, Relative cover, Density, Relative density and Important value were determined. The highest IVI value recorded in this study were that of Dactylocteniumaegyptium(0.9287), Paspalumconjugatum (0.6651) and Brachiarialata(0.6428) meaning they were dominant in among the observed members of the Poaceaefamily. And the lowest IVI value observed was that of Sorghum bicola (0.0209). The IVI value ranged between 0.0209 to 0.9287. This studyprovide baseline information about Poaceae in Bauchi State University Gadau Main Campus which is represented by 8 specie with 7 genera and almost total appearance of 894.